2021
DOI: 10.1037/hea0001047
|View full text |Cite
|
Sign up to set email alerts
|

Negative affect and self-agency’s association with immunosuppressant adherence in organ transplant: A meta-analysis.

Abstract: In organ transplant, prevalence estimates of negative affect (e.g., depressive symptoms) are higher than in the general population and self-agency is required for successful regimen selfmanagement. Nonetheless, the roles of these psychological factors for immunosuppressant adherence in this population remain unclear. Method: Meta-analytic techniques were used to determine the associations between negative affect and self-agency with adherence and to identify moderators of these associational effect sizes (ES).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 62 publications
(97 reference statements)
0
12
0
1
Order By: Relevance
“…In the context of our secondary analysis, we identified 41 records from a total pool of included 742 scoping review records contained definitions. Screening of these records resulted in eight “original” definitions [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Sixty three records were identified through secondary sources [ 20 , 21 , 23 , 25 , 26 , 28 , 30 , 31 , 33 , 34 , 35 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of our secondary analysis, we identified 41 records from a total pool of included 742 scoping review records contained definitions. Screening of these records resulted in eight “original” definitions [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Sixty three records were identified through secondary sources [ 20 , 21 , 23 , 25 , 26 , 28 , 30 , 31 , 33 , 34 , 35 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
“…A single definition focused on an aspect of SM medication adherence [ 44 ], and the remainder focused on all aspects. Definitions focused on one or multiple transplant organ types: heart [ 46 , 49 , 50 ], liver [ 45 , 48 , 49 ], kidney [ 44 , 45 , 49 , 51 ], pancreas [ 49 ], and lung [ 49 ] ( Supplementary File S2 ). Amongst the definition publications, seven of the eight are quantitative studies, with one qualitative [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological issues like depression and negative affect are seen in higher rates in transplant patients than in the general public. A meta-analysis of 50 studies found that negative affect was associated with nonadherence, whereas self-agency was associated with better adherence [31 ▪ ]. In a sample of pediatric transplant patients, posttraumatic stress symptoms were associated with nonadherence in adolescent liver transplant recipients [32 ▪ ].…”
Section: General Updatesmentioning
confidence: 99%